2021
DOI: 10.3390/ijms222312851
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Hydroxylase 2 Deficiency Modifies the Effects of Fluoxetine and Pargyline on the Behavior, 5-HT- and BDNF-Systems in the Brain of Zebrafish (Danio rerio)

Abstract: The mechanisms of resistance to antidepressant drugs is a key and still unresolved problem of psychopharmacology. Serotonin (5-HT) and brain-derived neurotrophic factor (BDNF) play a key role in the therapeutic effect of many antidepressants. Tryptophan hydroxylase 2 (TPH2) is the rate-limiting enzyme in 5-HT synthesis in the brain. We used zebrafish (Danio rerio) as a promising model organism in order to elucidate the effect of TPH2 deficiency caused by p-chlorophenylalanine (pCPA) on the alterations in behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The novel tank test allows the evaluation of the vertical exploratory behavior of a fish introduced into a new environment (e.g., a new aquarium), considering several different parameters such as swimming distance, speed, latency for free swimming (time between introduction and movement/ exploration of the aquarium), freezing behavior, time and number of entries at different areas of the tank (e.g., bottom, middle, top). In general, several studies that used D. rerio (embryos and adults) and O. latipes (medaka) adults, testing concentrations from 0.004 to 10,000 μg/L and different exposure periods (from 3 min to 30 days), showed decreased stress levels after fluoxetine exposure (Abreu et al, 2016a;Ansai et al, 2016;Evsiukova et al, 2021;Farias et al, 2020;Giacomini et al, 2016;Pittman and Hylton, 2015;Pittman and Ichikawa, 2013;Singer et al, 2016;Vera-Chang et al, 2018Wong et al, 2013). Overall, an increase in the exploratory behavior, with fish swimming longer at the top of the tank, decreases in freezing, lower latency to enter the top area and higher mean speed has been reported.…”
Section: Locomotor Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The novel tank test allows the evaluation of the vertical exploratory behavior of a fish introduced into a new environment (e.g., a new aquarium), considering several different parameters such as swimming distance, speed, latency for free swimming (time between introduction and movement/ exploration of the aquarium), freezing behavior, time and number of entries at different areas of the tank (e.g., bottom, middle, top). In general, several studies that used D. rerio (embryos and adults) and O. latipes (medaka) adults, testing concentrations from 0.004 to 10,000 μg/L and different exposure periods (from 3 min to 30 days), showed decreased stress levels after fluoxetine exposure (Abreu et al, 2016a;Ansai et al, 2016;Evsiukova et al, 2021;Farias et al, 2020;Giacomini et al, 2016;Pittman and Hylton, 2015;Pittman and Ichikawa, 2013;Singer et al, 2016;Vera-Chang et al, 2018Wong et al, 2013). Overall, an increase in the exploratory behavior, with fish swimming longer at the top of the tank, decreases in freezing, lower latency to enter the top area and higher mean speed has been reported.…”
Section: Locomotor Behaviormentioning
confidence: 99%
“…This decreased mRNA expression may impair neurotransmission, leading to behavioral changes (Dzieweczynski et al, 2016;Pelli and Connaughton, 2015;Winder et al, 2012). Evsiukova et al (2021) observed that a 72-h exposure to 200 μg/L fluoxetine (and the combined effect of 200 μg/L fluoxetine with 2000 μg/L an irreversible TPH2 inhibitor p-chlorophenylalanine (pCPA)), resulted in a significant decrease in the mRNA levels of tryptophan hydroxylase 2 (tph2) and serotonin receptor 2A (htr2aa) genes in the brain of adult D. rerio exposed. Theodoridi et al (2017) reported up-regulated levels of serotonin receptor 2b (htr2b) in the brain of adult D. rerio (dominant and submissive) exposed, for 2 h, to 5000 μg/L fluoxetine.…”
Section: Genes Related To Serotonin Neurotransmission: Transporters A...mentioning
confidence: 99%
“…The deficit of the TPH activity results in a dramatic decrease in the 5-HT and 5-HIAA levels in the brain of mice [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. An irreversible inhibitor of TPH, p-chlorophenylalanine, dramatically decreases the 5-HT and 5-HIAA levels in the brain of zebrafish [ 46 , 47 ]. Secondly, an MAO inhibitor, pargyline, dramatically increases the 5-HT level and decreases the 5-HIAA concentration in the brain of zebrafish [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…An irreversible inhibitor of TPH, p-chlorophenylalanine, dramatically decreases the 5-HT and 5-HIAA levels in the brain of zebrafish [ 46 , 47 ]. Secondly, an MAO inhibitor, pargyline, dramatically increases the 5-HT level and decreases the 5-HIAA concentration in the brain of zebrafish [ 46 , 47 ]. Therefore, the age-related decrease in TPH activity and increase in MAO activity together accelerate the observed age-dependent decrease in the 5-HT levels in killifish brain.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study highlights the relationship between TPH2 expression and BDNF levels. The administration of a pargyline (MAO inhibitor) in zebrafish treated with an irreversible inhibitor of TPH2 (p-chlorophenylalanine) led to reduced BDNF levels, revealing an interdependence between 5-HT and BDNF systems in the antidepressant response [ 112 ]. The interaction between 5-HT neurotransmission and the BDNF-related pathways was also supported by another study.…”
Section: Trp Metabolism In Depression—an Overlookmentioning
confidence: 99%